Measurement of strong electromagnetic pulses generated from solid targets at sub-ns kJ-class PALS laser facility. (29th June 2021) - Rączka, P; Cikhardt, J; Pfeifer, M; Krása, J; Krupka, M; Burian, T; Krůs, M; Pisarczyk, T; Dostál, J; Dudžák, R; Badziak, J
Abstract: Measurements had been performed of strong electromagnetic pulses (EMPs) generated as a result of laser–target interaction at the sub-ns kJ-class Prague Asterix Laser System facility. Two conductive Prodyn FD5C D-dot pencil probes were used. Measurements were performed inside the experimental chamber and outside the chamber in a large chamber window 40 cm in diameter in a setup that guaranteed 6 GHz bandwidth. A very good signal-to-noise ratio (17:1) was obtained after some steps were taken to ensure proper EMP shielding of the data collection setup. The EMP signal in the time domain was found to have the form of a sharp initial spike followed by gradually decaying oscillations interspersed with some secondary spikes. The values of the vertical component of the electric field strength were estimated. The highest value recorded in this experiment was 620 − 180 + 260 kV m −1 at a distance of 40 cm from the target. It was observed that plastic targets—particularly the 100s of µ m thick plastic foils—tend to generate stronger EMP fields than Cu and Au targets. A time-frequency analysis was performed for a typical shot, clearly showing some spectral features that appear only sometime after the start of the signal and hence indicate EMP generation from secondary sources. Electrons ejected from the target were recorded with the energies exceeding 1.5 MeV, which indicates that highly energetic processes are triggered as a result of the laser–target interaction.